Evaluation of awareness, requirement, and clinical applications of guided endodontics among dental practitioners in North India – A cross-sectional study - Dakshita Joy Sinha; Jayati Pandey; Mansi Kumari; Geetika Arora; Mayura Paul; Rahul Paul (Endodontology)
Aim: Guided endodontics (GE) represents a cutting-edge shift in dental practice, utilizing three-dimensional imaging to enhance treatment precision and safety in endodontics. Since its introduction in 2016, GE has shown promise in reducing complications by guiding dental procedures with minimal invasiveness. This study evaluates its acceptance and application among North India’s dental community, aiming to identify educational gaps and operational challenges. Methods: An online survey, approved by ethical standards, was distributed to dental professionals in North India, collecting 265 responses on their familiarity, application, and training needs regarding GE. Results: Findings reveal a general awareness of GE among respondents, with a notable lack of specialized training. While GE’s benefits in various dental treatments were acknowledged, a significant interest in further training was expressed, underlining the necessity for enhanced educational programs. Conclusion: The research highlights a keen interest in GE among dentists, despite existing educational gaps. There is a clear call for integrating GE-focused training into dental curricula to equip practitioners with the skills needed for its effective use, potentially transforming patient care in endodontics.